Developmental vulnerability at age five among children who enter and progress through the child protection system in New South Wales, Australia: a cross-sectoral data linkage study - Falster, Kathleen; Hanly, Mark; Pilkington, Rhiannon; Chilvers, Marilyn; Whittaker, Elizabeth; Lynch, John (International Journal of Population Data Science, 2018)
Introduction A recent independent review of the child protection system in New South Wales (NSW), Australia, highlighted the need for whole-of-government reform to improve outcomes for children at risk of, or experiencing, maltreatment. Population-level evidence on outcomes of children who enter and progress through the child protection system is currently lacking. Objectives and Approach We aimed to quantify developmental vulnerability at age five among children who enter and progress through the child protection system during early childhood to demonstrate the value of cross-sectoral data linkage to inform and evaluate policy at a population-level. We used Australian Early Development Census (AEDC) data linked to cross-sectoral population datasets in NSW, including birth registrations, perinatal, and child protection notification and out-of-home care (OOHC) placement data. Linked AEDC data, collected in 2009 and 2012, are available for 153,670 NSW children. Socio-demographic and perinatal characteristics available in the linked data were used to characterise the population. Results 21,179 (13.9%) children had ≥1 ‘screened in’ notification, 4927 (3.2%) had ≥1 substantiated abuse and neglect notification, and 2177 (1.4%) had ≥1 OOHC placement before their fifth birthday. Indicators of disadvantage and adverse birth outcomes were more common among children who progressed to higher levels of the child protection system. The proportion developmentally vulnerable on ≥1 domains of the AEDC increased for children who entered and progressed through the child protection system; from 21% of children with no contact with child protection before age five, to 39% of children with ≥1 ‘screened in’ notification, 50% with ≥1 substantiated notification, and 54% with ≥1 OOHC placement before their fifth birthday. Comparison of findings from other Australian jurisdictions with similar data will be discussed. Conclusion/Implications This study demonstrates there is scope to improve developmental outcomes through targeted interventions among children who become known to child protection during early childhood in NSW. Moreover, it illustrates that cross-sectoral data linkage can be used to inform and evaluate policy reforms to drive better outcomes for vulnerable children.